Statistics in medicine - Riffenburgh, R. H. (Robert H.) (Elsevier/Academic Press, 2012)
Makes medical statistics easy to understand for students, practicing physicians, and researchers. This book begins with databases from clinical medicine and uses such data to give multiple worked-out illustrations of every method.